2022
DOI: 10.3390/ma15082917
|View full text |Cite
|
Sign up to set email alerts
|

Experimental Study on Chloride Ion Diffusion in Concrete Affected by Exposure Conditions

Abstract: The transport mechanism of chloride ions in concrete is relatively complicated since the erosion process is influenced by many factors. To investigate the effect of exposure conditions on the chloride ion diffusion property, three exposure conditions (long-term immersion in static sodium chloride solution, long-term immersion in circulating sodium chloride solution and dry–wet cycles in circulating sodium chloride solution) were considered in chloride ion diffusion experiments. Experimental results indicated t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(4 citation statements)
references
References 38 publications
0
4
0
Order By: Relevance
“…96 The inuence of different conditions for the measurements was investigated by Qu et al, who found small variations between static exposure to chlorine solution, owing exposure, and owing exposure combined with dry-wet cycles. 98 A comparison of the performance of different surface treatments in preventing chloride diffusion is summarized in Fig. 7.…”
Section: Chloride Permeabilitymentioning
confidence: 99%
See 1 more Smart Citation
“…96 The inuence of different conditions for the measurements was investigated by Qu et al, who found small variations between static exposure to chlorine solution, owing exposure, and owing exposure combined with dry-wet cycles. 98 A comparison of the performance of different surface treatments in preventing chloride diffusion is summarized in Fig. 7.…”
Section: Chloride Permeabilitymentioning
confidence: 99%
“…96 The influence of different conditions for the measurements was investigated by Qu et al , who found small variations between static exposure to chlorine solution, flowing exposure, and flowing exposure combined with dry–wet cycles. 98…”
Section: Comparison Of Surface Treatment Performancesmentioning
confidence: 99%
“…There are various diffusion modes of chloride in concrete, and the transmission of chloride is considered to be dominated by diffusion mechanism within the peak chloride content. Therefore, Fick's second law is used to describe the diffusion process of chloride in marine environment in concrete, and the analytical solution can be expressed by Equation 4 [28].…”
Section: Chloride Diffusion Modelmentioning
confidence: 99%
“…The research team of the authors of this paper investigated the influences of different compositions of recycled aggregates [22], high-volume fly ash and fine-grinding fly ash [23,24], and blended mineral admixture [25] on the workability, durability, and mechanical properties of concrete and its durability exposed in a severe environment [26]. This provides a foundation for investigating the preparation of self-compacting UNC.…”
Section: Introductionmentioning
confidence: 99%